The cytotoxic effects of sertraline on ovarian (A2780) cancer cells in vitro - Amini Khodashahri, Fatemeh; Zargarnezhad, Marjan; Sajadi, Rojina (Journal of Biological Studies, 2022)
A number of studies have shown that antidepressants can affect cancer cells viability, however, there are few studies focusing on anticancer effects of sertraline on ovarian cancer cells. Therefore, the aim of this study was to investigate the effects of sertraline on cell viability in ovarian (A2780) cancer cells. A2780 cells were divided into control group and groups treated with 1.5625, 3.125, 6.25, 12.5, 25, 50 and 100 μg/ml of sertraline. 24 and 48 hours after treatment, cell viability was assessed by MTT assay method. Data were analyzed using one-way analysis of variance. Treatment with 6.25, 12.5, 25, 50 and 100 μg/ml of sertraline led to significant decrease in cell viability compared to control group 24 and 48 hours after treatment. Although treatment of A2780 cells with 3.125 μg/ml of sertraline did not significantly change the cell viability 24h after treatment, however, treatment of A2780 cells with 3.125 μg/ml of sertraline for 48h significantly decreased the cell viability compared to control group. IC50 value was 11.6 and 5.8 μg/ml for sertraline 24 and 48 hours after treatment, respectively, showing a significant decrease in IC50 (48h) compared to IC50 (24h). The results of this study revealed that sertraline has cytotoxic effects on ovarian cancer cells in vitro. Increased treatment duration led to enhanced cytotoxicity of sertraline on ovarian cancer cells.